Effect of Access to Capital, Entrepreneurship Education, and HR Competencies on Start-up Success in the Technology Sector - Loso Judijanto; Sri Dewi Lisnawaty (Westscience Press, 2024)
This study examines the impact of access to capital, entrepreneurship education, and human resource (HR) competencies on the success of start-ups in the technology sector. Utilizing a quantitative approach, data were collected from 150 start-up firms through structured questionnaires using a Likert scale ranging from 1 to 5. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicate that all three factors—access to capital, entrepreneurship education, and HR competencies—positively and significantly influence start-up success. Access to capital allows start-ups to invest in research and development, scale operations, and attract top talent, while entrepreneurship education equips entrepreneurs with essential skills for strategic decision-making. HR competencies, as the strongest predictor, underscore the critical role of a skilled workforce in driving innovation and sustaining growth in the technology sector. The findings provide valuable insights for entrepreneurs, educators, and policymakers seeking to support the development and success of technology start-ups.